Noise Characterization in InAlAs/InGaAs/InP pHEMTs for Low Noise Applications - Z. A. Djennati; K. Ghaffour (International Journal of Electrical and Computer Engineering (IJECE), 2017)
In this paper, a noise revision of an InAlAs/InGaAs/InP psoeudomorphic high electron mobility transistor (pHEMT) in presented. The noise performances of the device were predicted over a range of frequencies from 1GHz to 100GHz. The minimum noise figure (NFmin), the noise resistance (Rn) and optimum source impedance (Zopt) were extracted using two approaches. A physical model that includes diffusion noise and G-R noise models and an analytical model based on an improved PRC noise model that considers the feedback capacitance Cgd. The two approaches presented matched results allowing a good prediction of the noise behaviour. The pHEMT was used to design a single stage S-band low noise amplifier (LNA). The LNA demonstrated a gain of 12.6dB with a return loss coefficient of 2.6dB at the input and greater than -7dB in the output and an overall noise figure less than 1dB.